(untitled) (Al-Mansour Journal, 2022)
The efficiency of any society is linked to the efficiency of the human element. Its ability and desire to work.Institutions today attach great importance to the management of human resources because of the conviction that human resources has the capacity to lead the institution to the achievement of the desired objectives if the right environment of work, attention and stimulation is created . And like all institutions, the Algerian ours seek to improve its national economy and this wouldn’t happen unless they meet the assigned roles to in the best way.and it Managers should take seriously the issue of incentives .because ignoring this issue will turn to a quite disastrous result .on the other hand if taken seriously this issue will encourage workers to take care and develop their will at work.